Pathways to Success: Latina Perspectives on Experiential Learning in Education - Rose Santos; Bolade Ajayi-Abitogun (Adult Education Research Conference, 2025)
This round table discusses Latina women’s experiences in education, focusing on their roles as students, workers, and family roles as mothers, daughters, and wives highlighting their challenges and opportunities.
Keywords: Latina Perspectives; Experiential Learning; Adult Education